1984
DOI: 10.2323/jgam.30.63
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pyrite oxidation III. Adsorption of Thiobacillus ferrooxidans cells on solid surfaces and its effect on iron release from pyrite.

Abstract: The cells of 'Thiobacillus ferrooxidans were rapidly adsorbed on the solid surfaces of an agitated flask containing 1 % pulp density of pyrite particles. More than ca. 99 % of the inoculated cells were adsorbed. However, considerably fewer cells were adsorbed on pyrite particles than on the glass wall of the flask. Scanning electron microscope observation revealed that T. ferrooxidans cells were adsorbed aggregatively on restricted areas of the pyrite particles. The surfaces of the pyrite particles were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 19 publications
(26 reference statements)
0
12
1
Order By: Relevance
“…However, rates of pyrite oxidation by T. ferrooxidans reported in the literature are difficult to compare, making difficult the evaluation of different bacterial strains and leaching processes. In some recent reports, rates of pyrite bioleaching by T. ferrooxidans range from 2.5 to 30 mg/liter (4,5,6,11,12,18,19). This variability in leaching rates might be due to physiological differences among strains of T. ferrooxidans, but it could also be due to variables associated with conducting and measuring bioleaching rates.…”
mentioning
confidence: 99%
“…However, rates of pyrite oxidation by T. ferrooxidans reported in the literature are difficult to compare, making difficult the evaluation of different bacterial strains and leaching processes. In some recent reports, rates of pyrite bioleaching by T. ferrooxidans range from 2.5 to 30 mg/liter (4,5,6,11,12,18,19). This variability in leaching rates might be due to physiological differences among strains of T. ferrooxidans, but it could also be due to variables associated with conducting and measuring bioleaching rates.…”
mentioning
confidence: 99%
“…T. ferrooxidans and T. thiooxidans cells are known to adsorb on solid surfaces even when they are killed by heat (19). The heat-killed T. thiooxidans cells virtually stopped the Fe2+ release from pyrite ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Strains Fe l and Fe2 belong to T. ferrooxidans. Fe l has often been used in our studies (25)(26)(27). However, strains Fel and Fe2 are different in their ability to oxidize sulfur and thiosulfate.…”
Section: Discussionmentioning
confidence: 99%
“…We studied the ecological aspects of acidophilic chemolithotrophic iron-and sulfur-oxidizing bacteria at the abandoned Matsuo sulfur and iron sulfide (pyrite) mine areas (21,22,24) and the leaching of pyrite ores by the bacteria (25)(26)(27). We found that iron-and sulfur-oxidizing bacteria were ubiquitously distributed in both acid mine waters and pyrite ores, and were responsible for the rapid oxidation of iron and sulfur and the degradation of the ores.…”
mentioning
confidence: 99%